THU0261 Continuous nsaid use reverts the effects of inflammation on radiographic progression in patients with ankylosing spondylitis. (23rd January 2014) - Kroon, F.; Landewé, R.; Dougados, M.; van der Heijde, D.
Abstract : Background: In a recent clinical trial it was shown that continued treatment with nonsteroidal anti-inflammatory drugs (NSAIDs), in comparison to on-demand use of NSAIDs, reduced radiological progression in the spine in patients with ankylosing spondylitis.(1) To improve the benefit-risk ratio it is crucial to understand which patients may have most to gain from continuous NSAID-use in terms of radiological progression. Objectives: The aim of this study was to compare continuous NSAID treatment and on-demand NSAID treatment with respect to their ability to suppress radiographic progression in subgroups of patients with elevated CRP-levels, elevated ESR, high ASDAS-levels or high BASDAI-levels in comparison to patients with normal levels. Methods: Post-hoc analyses were performed in the above referenced RCT. Relevant subgroups were created by splitting the groups at predefined values considered as high/elevated based on time-averaged (ta) CRP (>5mg/L), ta-ESR (>12mm/hr), ta-BASDAI (>4), ta-ASDAS-CRP (>2.1) and ta-ASDAS-ESR (>2.1). Subgroups were further split according to NSAID-use (continuous vs. on-demand). Statistical interactions were tested using multiple regression analysis. Differences in radiological progression between groups were analysed using the Chi-square and Mann-Whitney U test. Results: 150 randomized patients (continuous-treatment group (n=76), on-demand group (n=74)) had complete radiographs and were included in the analyses. The effect of slowing radiological progression, both as continuous dmSASSS or % patients progressing ≥2 mSASSS, with continuous NSAID therapy was more pronounced in patients with elevated ta-CRP-levels, elevated ta-ESR, high ta-ASDAS-CRP or high ta-ASDAS-ESR versus patients with low/normal values (p<0.05) (Table). No such effect was found for patients with high vs. low BASDAI. In patients with elevated ta-ESR (irrespective of treatment), structural progression was higher than in patients with normal ta-ESR (p<0.01). Regression analyses showed that continuous NSAID treatment neutralizes the deleterious effects of inflammation (high ta-ESR) (no statistical interaction). Conclusions: Patients with elevated acute phase reactants benefit most from continuous NSAID treatment. Prioritizing patients with elevated acute phase reactants for continuous NSAID-treatment may improve the benefit-risk-ratio, of NSAID-treatment in AS. References: Wanders A et al. Arthritis Rheum. 2005;52:1756-65 Disclosure of Interest: None Declared